2023
DOI: 10.1002/ana.26593
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Synaptic Density PET with 11C‐UCB‐J 6 Months After Ischemic Stroke

Abstract: Objective The purpose of this study was to explore longitudinal changes in synaptic density after ischemic stroke in vivo with synaptic vesicle protein 2A (SV2A) positron emission tomography (PET). Methods We recruited patients with an ischemic stroke to undergo 11C‐UCB‐J PET/MR within the first month and 6 months after the stroke. We investigated longitudinal changes of partial volume corrected 11C‐UCB‐J standardized uptake value ratio (SUVR; relative to centrum semiovale) within the ischemic lesion, peri‐isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Two studies of human ischemic stroke patients have shown that synaptic density decreases within 1 month after stroke and further declines over time. 6,7 Yan et al 8 showed that in both middle cerebral artery occlusion (MCAO) and oxygen-glucose deprivation (OGD) mouse models of ischemia, synaptosome-associated protein 29 (SNAP- 29) protein was expressed at low levels, and the volume of the presynaptic readily releasable pool (RRP) was reduced, which resulted in abnormal neurological function. Haghani et al 9 found that mild ischemia significantly increased basal synaptic transmission based on field potential recordings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies of human ischemic stroke patients have shown that synaptic density decreases within 1 month after stroke and further declines over time. 6,7 Yan et al 8 showed that in both middle cerebral artery occlusion (MCAO) and oxygen-glucose deprivation (OGD) mouse models of ischemia, synaptosome-associated protein 29 (SNAP- 29) protein was expressed at low levels, and the volume of the presynaptic readily releasable pool (RRP) was reduced, which resulted in abnormal neurological function. Haghani et al 9 found that mild ischemia significantly increased basal synaptic transmission based on field potential recordings.…”
Section: Introductionmentioning
confidence: 99%
“…After ischemic stroke, entire or specific regions of the brain become ischemic and hypoxic, which causes neuronal and synaptic damage and leads to neurological dysfunction. Two studies of human ischemic stroke patients have shown that synaptic density decreases within 1 month after stroke and further declines over time 6,7 . Yan et al 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in vivo visualization and quantitative analysis of synaptic density offer extensive clinical applications in the diagnosis, treatment monitoring, and mechanistic research of neurological and psychiatric disorders as well as tumors like NED in NETs (Cai et al, 2019). Up to now, Positron emission tomography (PET) imaging of SV2A has a tremendous potential to be utilized as an early-stage biomarker for Alzheimer's disease (AD) (Mecca et al, 2020) (Mecca et al, 2022), Parkinson's disease (PD) (Delva et al, 2020) (Martin et al, 2023), epilepsy (Tang et al, 2022), autism (Bourgeron, 2015), stroke (Michiels et al, 2023) (Michiels et al, 2022), traumatic brain injury (Jamjoom et al, 2021) and Spinocerebellar Ataxia Type 3 (Chen et al, 2023), as well as psychiatric disorders such as schizophrenia and depression in human subjects (Holmes et al, 2019), including In order to conduct a broader and more in-depth investigation into clinical diseases related to SV2A expression, developing a safe and stable multi-dose [ 18 F] SynVesT-1 radioactive imaging agent production process is of great signi cance. Kenneth Dahl and the co-workers had fully automated radiosynthesis of [ 18 F] SynVesT-1, which performed according to good manufacturing procedure (GMP) using a commercially available module (TracerMaker, ScanSys Laboratorieteknik ApS, Copenhagen, Denmark) with minor changes, and result a highyield, acceptance criteria and quality control (Dahl et al, 2022).…”
Section: Introductionmentioning
confidence: 99%